A 6-year surveillance study of "Stingers" in NCAA American Football. Issue 1 (2nd January 2017) - Green, James; Zuckerman, Scott L.; Dalton, Sara L.; Djoko, Aristarque; Folger, Dustin; Kerr, Zachary Y.
ABSTRACT: This study describes the epidemiology of "stinger" injuries in National Collegiate Athletic Association (NCAA) Men's Football. About 57 NCAA Men's Football programmes provided 153 team-seasons of injury data to the NCAA Injury Surveillance Programme (NCAA-ISP) during the 2009/2010–2014/2015 academic years. In the study period, 229 "stingers" were reported for an injury rate of 2.04/10, 000 athlete-exposures (AE). Most "stingers" were reported during competitions (55.5%) and the preseason (80.3%) and resulted in time loss less than 24 hours (63.8%). One in five (18.8%) were recurrent. Most "stingers" were due to player contact (93.0%), particularly while tackling (36.7%) and blocking (25.8%) and occurred to defensive ends/linebackers (25.8%) and offensive linemen (23.6%). Although previous research reports a large prevalence of "stingers" among football players, the NCAA-ISP reported a relatively low injury rate. The transient nature of pain associated with "stingers" may have contributed to under-reporting, highlighting the need to deduce manners to increase reporting.